2015
DOI: 10.1097/wnr.0000000000000330
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of EEG visual-evoked potentials in rats through neuromodulatory focused ultrasound

Abstract: We investigated the use of pulsed low-intensity focused ultrasound (FUS) to suppress the visual neural response induced by light stimulation in rodents. FUS was administered transcranially to the rat visual cortex using different acoustic intensities and pulsing duty cycles. The visual evoked potentials (VEP) generated by an external strobe light stimulation were measured three times before, once during, and five times after the sonication. The VEP magnitude was suppressed during the sonication using a 5% duty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(108 citation statements)
references
References 18 publications
9
99
0
Order By: Relevance
“…As reported by Min et al , ultrasound may induce a suppression of seizure activity [21] and EEG based visual evoked response potentials [47]. Since calcium imaging is an imaging modality that relies on neural depolarization, neural suppression, characterized by a lack of depolarization, is difficult to observe due to the lack of increase in intracellular calcium.…”
Section: Tfus Indirectly Activates Auditory Cortex and Subsequently Pmentioning
confidence: 99%
“…As reported by Min et al , ultrasound may induce a suppression of seizure activity [21] and EEG based visual evoked response potentials [47]. Since calcium imaging is an imaging modality that relies on neural depolarization, neural suppression, characterized by a lack of depolarization, is difficult to observe due to the lack of increase in intracellular calcium.…”
Section: Tfus Indirectly Activates Auditory Cortex and Subsequently Pmentioning
confidence: 99%
“…Ultrasound neuromodulation has been successfully performed transcranially in various animal species, including mice (King et al 2013; King et al 2014; Mehić et al 2014; Tufail et al 2010), rats (Kim et al 2012; Kim et al 2014; Kim et al 2015; Min et al 2011; Younan et al 2013), sheep (Lee et al 2016), monkeys (Deffieux et al 2013), and even humans (Lee et al 2015; Legon et al 2014). Histological techniques have confirmed that it is possible to deliver sonications powerful enough to elicit ultrasound neuromodulation without causing damage to tissues (Tufail et al 2010; Yoo et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The acoustic neuromodulatory effects can be tailored as either excitatory or suppressive, depending on the sonication parameters [11, 12]. Accumulating ex vivo [13, 14] and in vivo [12, 1518] evidence shows that acoustic pressure waves delivered to localized brain structures modulate their excitability using low-level acoustic intensity (i.e., compatible with potential human application [19, 20]).…”
Section: Introductionmentioning
confidence: 99%